2001
DOI: 10.1111/j.0014-3820.2001.tb00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Deleterious Mutations in Clonal Lineages: Evidence From Hybridogenetic Frogs

Abstract: Abstract. The hemiclonal waterfrog Rana esculenta (RL genotype), a bisexual hybrid between R. ridibunda (RR) and R. lessonae (LL), eliminates the L genome from its germline and clonally transmits the R genome (hybridogenesis). Matings between hybrids produce R. ridibunda offspring, but they generally die at an early larval stage. Mortality may be due to fixed recessive deleterious mutations in the clonally inherited R genomes that were either acquired through the advance of Muller's ratchet or else frozen in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…Finally, in some species, only one half of the genome (maternal or paternal) is retained in the germline without recombination. This phenomenon is called hybridogenesis [63] and has been well documented for the hemiclonal waterfrogs Rana esculenta, in which either the maternal or paternal genome may be retained [64]. In maternal hybridogenesis, male sperm of one parental species is still needed.…”
Section: Definition and Limits For Asexual Reproductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in some species, only one half of the genome (maternal or paternal) is retained in the germline without recombination. This phenomenon is called hybridogenesis [63] and has been well documented for the hemiclonal waterfrogs Rana esculenta, in which either the maternal or paternal genome may be retained [64]. In maternal hybridogenesis, male sperm of one parental species is still needed.…”
Section: Definition and Limits For Asexual Reproductionmentioning
confidence: 99%
“…Vol. 64,2007 Review Article produced can stay attached to the mother plant, in which case they can be considered as branches of the same individual. This is different from the production of independent individuals.…”
Section: Description Of Different Forms Of Clonal Reproduction and LImentioning
confidence: 99%
See 1 more Smart Citation
“…They thus depend on backcrossing with R. lessonae to form a new generation of hybrids (L-E system). Inter-hybrid matings usually result in RR offspring that are inviable because they are homozygous for recessive deleterious mutations in the clonally transmitted R genome (Vorburger, 2001a). Modifications of this system include reproduction with P. ridibundus instead of P. lessonae in eastern Europe (R-E system), triploid LLR and LRR individuals (can be present in all breeding systems) and the allhybrid populations (E-E system).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that non-hybrids (LL and RR) arise from hybrid  hybrid matings, but die off during larval stages (Christiansen et al, 2005;Arioli, 2007, Chapter 3). The inviability of RR offspring from hybrid  hybrid matings in the L-E system arises from the diploid hybrids' clonal mode of reproduction (Vorburger, 2001a), but this explanation cannot hold for all-hybrid populations where recombination between the two Ls occurs in LLR frogs and between the two Rs in LRR frogs (Christiansen and Reyer, 2009). An alternative hypothesis is that genetic diversity in the L and R genomes within all-hybrid populations is so low that, despite regular recombination within them, LL and RR offspring nevertheless become homozygous for a sufficient number of recessive deleterious mutations to kill them.…”
Section: Introductionmentioning
confidence: 99%